Peran Pembelajaran IPS Dalam Membentuk Sikap Kewirausahaan Siswa di SMPN 2 Rangsang Pesisir - Miftahul Shulha Badriyah; Yudi Irwan (EL-EMIR Institute, 2025)
Social studies education at the junior high school level plays a crucial role in instilling the values ​​of independence, creativity, and responsibility as the foundation for entrepreneurial attitudes from an early age. The urgency of this research is based on students' low interest and understanding of entrepreneurial concepts, particularly in linking social studies material to everyday life practices. This study aims to analyze the role of social studies learning in shaping students' entrepreneurial attitudes at SMPN 2 Rangsang Pesisir. The method used was a descriptive qualitative approach, with data collection techniques through observation, interviews, and documentation. The study subjects included two social studies teachers and 119 students in grades VIII, VIII, and IX. The results indicate that social studies learning contributes to fostering creativity, independence, self-confidence, and risk-taking attitudes in students, particularly through discussion methods, case studies, and simple, practice-based projects. However, its implementation still faces obstacles such as limited time, facilities, and hands-on experience. Therefore, more contextual and applicable learning innovations are needed to strengthen the development of students' entrepreneurial attitudes in a sustainable manner.